Electromagnetic wave absorptive nonwoven fabric, article containing electromagnetic wave absorptive nonwoven fabric and sound absorber

The laminate structure of the electromagnetic wave absorbing nonwoven fabric, featuring specific fiber diameters and conductive polymer distribution, addresses bending durability and air permeability issues, ensuring effective high-frequency wave absorption and sound absorption.

JP2025013042APending Publication Date: 2025-01-24エムエーライフマテリアルズ株式会社
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023116318
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-07-14
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

Existing electromagnetic wave absorbing nonwoven fabrics face issues with bending durability and air permeability, particularly when exposed to high-frequency electromagnetic waves, leading to potential breakage and reduced performance.

Method used

A laminate structure comprising a first spunbond layer with an average fiber diameter of 20 μm to 50 μm, a second meltblown layer with a smaller diameter, and a conductive polymer attachment with controlled adhesion, ensuring air permeability between 5.0 cc/cm²·sec to 48.0 cc/cm²·sec, and embossed parts to maintain uniform polymer distribution.

Benefits of technology

The laminate structure provides excellent electromagnetic wave absorption and bending durability, maintaining performance even in environments where bending occurs, with improved air permeability and sound absorption properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025013042000002
    Figure 2025013042000002
  • Figure 2025013042000003
    Figure 2025013042000003
  • Figure 2025013042000004
    Figure 2025013042000004
Patent Text Reader

Abstract

To provide an electromagnetic wave absorptive nonwoven fabric excellent in electromagnetic wave absorptivity for electromagnetic wave in a high frequency band and bending durability.SOLUTION: An electromagnetic wave absorptive nonwoven fabric has a laminate to which conductive polymer is attached. The laminate has a first spun-bonded layer (A) and a second melt-blown layer (B). Average fiber diameter of the first spun-bonded layer (A) is 20 μm to 50 μm. Average fiber diameter of the second melt-blown layer (B) is smaller than the average fiber diameter of the first spun-bonded layer (A). The first spun-bonded layer (A) is one outermost layer of the laminate. Permeability is 5.0 [cc / cm2 sec] to 48.0 [cc / cm2 sec].SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to an electromagnetic wave absorbing nonwoven fabric, an article containing the electromagnetic wave absorbing nonwoven fabric, and a sound absorbing material. [Background technology]

[0002] In recent years, electromagnetic wave absorbing nonwoven fabrics that absorb electromagnetic waves generated from electronic devices have come into use.

[0003] Patent Document 1 discloses an electromagnetic wave absorbing adhesive sheet (hereinafter also referred to as "electromagnetic wave absorbing nonwoven fabric"). The electromagnetic wave absorbing nonwoven fabric disclosed in Patent Document 1 comprises a specific base material, a second resin layer containing soft magnetic particles, and an adhesive layer. As the second resin layer, a resin layer in which a soft magnetic material is dispersed in silicone rubber ("Bastaraid (registered trademark)" (product number FG1 (50), 50 μm thick, Tokin Corporation) (hereinafter also referred to as "noise suppression sheet") is specifically disclosed. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2020-013848 A Summary of the Invention [Problem to be solved by the invention]

[0005] However, when the electromagnetic wave-absorbing nonwoven fabric disclosed in Patent Document 1 is repeatedly folded back and forth, there is a risk that the electromagnetic wave-absorbing nonwoven fabric will break if the number of folding back and forth is less than 10,000. "Folding back and forth" refers to folding a test piece completely back and forth once on the same line. In other words, there is a risk that the bending durability of the electromagnetic wave-absorbing nonwoven fabric disclosed in Patent Document 1 is insufficient. Therefore, the applications of the electromagnetic wave-absorbing nonwoven fabric disclosed in Patent Document 1 are limited.

[0006] Furthermore, in recent years, the development of fifth-generation mobile communication systems (5G) has progressed, and there is a demand for electromagnetic wave absorbing nonwoven fabrics that have excellent electromagnetic wave absorbing properties for electromagnetic waves in high frequency bands (for example, 5 GHz).

[0007] For example, an electromagnetic wave absorbing nonwoven fabric including a nonwoven fabric attached to a conductive polymer is formed by applying a paint including a conductive polymer to the nonwoven fabric. However, in a nonwoven fabric having a conventional structure, when the paint is applied, the gaps between the fibers of the nonwoven fabric are filled with the paint, which may cause clogging of the nonwoven fabric. Therefore, the air permeability of the conventional electromagnetic wave absorbing nonwoven fabric may be low. Therefore, the applications of the conventional electromagnetic wave absorbing nonwoven fabric are limited.

[0008] The present disclosure has been made in view of the above, and aims to provide an electromagnetic wave-absorbing nonwoven fabric, an article containing the electromagnetic wave-absorbing nonwoven fabric, and a sound-absorbing material that are excellent in electromagnetic wave absorption and bending durability against electromagnetic waves in a high frequency band. The present disclosure aims to provide an electromagnetic wave-absorbing nonwoven fabric, an article containing the electromagnetic wave-absorbing nonwoven fabric, and a sound-absorbing material that can maintain good electromagnetic wave absorption performance and sound absorption function even in an environment where bending may occur. [Means for solving the problem]

[0009] Means for solving the above problems include the following embodiments. <1> a laminate having a conductive polymer attached thereto; The laminate comprises: A first spunbond layer (A) having an average fiber diameter of 20 μm to 50 μm; A second meltblown layer (B) having an average fiber diameter smaller than that of the first spunbond layer (A); having the first spunbond layer (A) is one outermost layer of the laminate, Air permeability is 5.0 [cc / cm 2 sec]~48.0[cc / cm 2 sec]. <2> The weight ratio (A) is 40% to 96%, The basis weight ratio (A) indicates a ratio of the basis weight of the first spunbond layer (A) to the basis weight of the laminate. <1> 2. The electromagnetic wave absorbing nonwoven fabric according to claim 1 . <3> The laminate has an average pore size of 5.0 μm or more. <1> or <2> 2. The electromagnetic wave absorbing nonwoven fabric according to claim 1 . <4> The laminate further includes a third spunbond layer (C) laminated on a side of the second meltblown layer (B) opposite to the first spunbond layer (A), The average fiber diameter of the third spunbond layer (C) is smaller than the average fiber diameter of the first spunbond layer (A). <1> ~ <3> 13. An electromagnetic wave-absorbing nonwoven fabric according to any one of the preceding claims. <5> The conductive polymer has a coating weight of 0.001 g / m 2 ~5.0g / m 2 and the weight of the conductive polymer in the third spunbond layer (C) is lower than the weight of the conductive polymer in the other layers; The other layer is a layer other than the third spunbond layer (C) among the layers included in the laminate. <4> 2. The electromagnetic wave absorbing nonwoven fabric according to claim 1 . <6> the laminate further comprises a fourth spunbond layer (D) between the first spunbond layer (A) and the second meltblown layer (B); The average fiber diameter of the fourth spunbond layer (D) is smaller than the average fiber diameter of the first spunbond layer (A). <1> ~ <5> 13. An electromagnetic wave-absorbing nonwoven fabric according to any one of the preceding claims. <7> The weight ratio (B) is 1% to 35%. The basis weight ratio (B) indicates a ratio of the basis weight of the second meltblown layer (B) to the basis weight of the laminate. <5> or <6> 2. The electromagnetic wave absorbing nonwoven fabric according to claim 1 . <8> The laminate has a plurality of embossed portions, The embossed area ratio of the laminate is 5% to 35%. <1> 2. The electromagnetic wave absorbing nonwoven fabric according to claim 1 . <9> The area of ​​each of the plurality of embossed portions is 0.1 mm2 ~1.5mm 2 The above <8> 2. The electromagnetic wave absorbing nonwoven fabric according to claim 1 . <10> The resin used in the laminate is a polyolefin resin. <1> ~ <9> 13. An electromagnetic wave-absorbing nonwoven fabric according to any one of the preceding claims. <11> The above <1> ~ <10> An electromagnetic wave absorbing nonwoven fabric-containing article comprising the electromagnetic wave absorbing nonwoven fabric described in any one of the above. <12> The above <1> ~ <10> 13. A sound-absorbing material comprising the electromagnetic wave-absorbing nonwoven fabric according to any one of the preceding claims. Effect of the Invention

[0010] According to the embodiments of the present disclosure, there are provided an electromagnetic wave absorbing nonwoven fabric, an article containing an electromagnetic wave absorbing nonwoven fabric, and a sound absorbing material that are excellent in electromagnetic wave absorption properties and bending durability against electromagnetic waves in a high frequency band. According to the embodiments of the present disclosure, there are provided an electromagnetic wave absorbing nonwoven fabric, an article containing an electromagnetic wave absorbing nonwoven fabric, and a sound absorbing material that can maintain good electromagnetic wave absorption performance and sound absorbing function even in an environment where bending may occur. [Brief description of the drawings]

[0011] [Figure 1A] FIG. 1A is a cross-sectional view of a laminate according to a first embodiment of the present disclosure. [Figure 1B] FIG. 1B is a cross-sectional view of the laminate according to the first embodiment of the present disclosure. [Figure 1C] FIG. 1C is a cross-sectional view of the laminate according to the first embodiment of the present disclosure. [Figure 1D] FIG. 1D is a cross-sectional view of the laminate according to the first embodiment of the present disclosure. [Figure 2A] FIG. 2A is an image of the front of the electromagnetic wave absorbing nonwoven fabric of Example 1 immediately after the conductive polymer paint was applied. [Figure 2B] FIG. 2B is an image of the front side of the electromagnetic wave absorbing nonwoven fabric of Example 1 after the conductive polymer paint has dried. [Diagram 3] FIG. 3 is an EPMA (electron probe microanalysis) image (magnification: 25 times) of the surface of the first spunbond layer (A) of the electromagnetic wave absorbing nonwoven fabric of Example 1. [Figure 4] FIG. 4 is a scanning electron microscope (SEM)-energy dispersive X-ray analyzer (EDX) image (magnification: 150 times) of a cross section of the electromagnetic wave-absorbing nonwoven fabric of Example 1 cut in the thickness direction. [Diagram 5] FIG. 5 is an image of the surface of the electromagnetic wave-absorbing nonwoven fabric of Comparative Example 2 after the conductive polymer paint has dried. [Figure 6] FIG. 6 is a graph showing the normal incidence sound absorption coefficient versus frequency for the electromagnetic wave-absorbing nonwoven fabrics of Example 9 and Comparative Example 6. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] In the present disclosure, the use of "to" indicating a numerical range means that the numerical values ​​before and after it are included as the lower limit and upper limit. In the present disclosure, in the ranges described stepwise, the upper or lower limit value described in one range may be replaced with the upper or lower limit value of another range described stepwise. In the ranges described in the present disclosure, the upper or lower limit value of the range may be replaced with the value shown in the examples. In the present disclosure, the term "step" refers not only to an independent step, but also to a step that cannot be clearly distinguished from other steps, as long as the intended purpose of the step is achieved. In this disclosure, when referring to the amount of each component in a composition, if multiple substances corresponding to each component are present in the composition, it means the total amount of multiple substances present in the composition, unless otherwise specified. In this disclosure, "nonwoven fabric" refers to a flat assembly of fibers that has a certain level of structural strength achieved by physical and / or chemical processes, excluding weaving, knitting, and papermaking. In this disclosure, "web" refers to a sheet composed solely of fibers. In this disclosure, "PEDOT / PSS" refers to a composite of poly(3,4-ethylenedioxythiophene) polystyrene (PEDOT) and polystyrene sulfonic acid (PSS).

[0013] (1) Electromagnetic wave absorbing nonwoven fabric The electromagnetic wave-absorbing nonwoven fabric of the present disclosure comprises a laminate to which a conductive polymer is attached. The laminate has a first spunbond layer (A) (hereinafter also referred to as "SB layer (A)") and a second meltblown layer (B) (hereinafter "MB layer (B)"). The average fiber diameter of the first spunbond layer (A) is 20 μm to 50 μm. The average fiber diameter of the second meltblown layer (B) is smaller than the average fiber diameter of the first spunbond layer (A). The first spunbond layer (A) is one of the outermost layers of the laminate. The air permeability is 5.0 [cc / cm 2 sec]~48.0[cc / cm 2 ·sec].

[0014] In the present disclosure, the term "conductive polymer" refers to a polymer that is conductive. "Conductive" refers to a state in which electricity flows, and refers to a polymer that has a sheet resistance of 1×10 or less as measured by a method conforming to JIS K 7194-1994 "Test method for resistivity of conductive plastics using a four-probe method." 8 It indicates that the resistance is lower than Ω / □. When electromagnetic waves (hereinafter simply referred to as "electromagnetic waves") in a high frequency band (for example, 5 GHz) are incident on a conductive polymer, the electromagnetic waves are converted into heat due to the electrical resistance of the conductive polymer. In other words, conductive polymers have the property of absorbing electromagnetic waves. "Spunbond layer" refers to a layer of spunbond nonwoven fabric. "Spunbond nonwoven fabric" refers to a nonwoven fabric made by one or more bonding methods to a web made by spinlay lamination. "Spinlay lamination" refers to a method of making a web by extruding molten or dissolved polymer through a nozzle and laying the filaments onto a moving screen. "Meltblown layer" refers to a layer of meltblown nonwoven fabric. Meltblown nonwoven fabric refers to a nonwoven fabric made by one or more bonding methods to a web made by meltblown lamination. "Meltblown lamination" refers to a method in which molten polymer is extruded into a high velocity hot gas stream into fibers that are then laminated onto a moving screen to create a web. "Air permeability" refers to the amount of air (cm ) that passes through an electromagnetic wave absorbing nonwoven fabric, measured by Method A (Fragile method) specified in the fabric testing method for woven and knitted fabrics (JIS L1096:2010). 3 / cm 2 ·s) is indicated.

[0015] The electromagnetic wave-absorbing nonwoven fabric of the present disclosure has the above-mentioned configuration and is therefore excellent in electromagnetic wave absorption properties and bending durability for electromagnetic waves in a high frequency band (for example, 5 GHz). This effect is believed to be due to, but not limited to, the following reasons. The conductive polymer is usually attached to the laminate by impregnating the laminate with a liquid containing the conductive polymer (hereinafter also referred to as a "conductive polymer paint"). In the present disclosure, the SB layer (A) is one of the outermost layers of the laminate. The average fiber diameter of the SB layer (A) is 20 μm to 50 μm. The average fiber diameter of the MB layer (B) is smaller than the average fiber diameter of the SB layer (A). The air permeability is 5.0 [cc / cm 2 sec]~48.0[cc / cm 2 ·sec]. In other words, the gaps between the fibers in the MB layer (B) inside the laminate are denser than the gaps between the fibers in the SB (A) layer, which is one of the outermost layers of the laminate. When the conductive polymer paint is impregnated from the SB(A) layer, excessive penetration of the conductive polymer paint into the laminate is suppressed. Therefore, the conductive polymer is likely to be uniformly attached to the fibers inside the laminate. As a result, it is speculated that the electromagnetic wave absorbing nonwoven fabric of the present disclosure has excellent electromagnetic wave absorption properties for electromagnetic waves. In particular, the conductive polymer "PEDOT / PSS" has been used for sensor applications in the past, but when "PEDOT / PSS" clogs the surface or inside of the laminate, the adhesion state to the fiber surface becomes uneven, and the continuity decreases, resulting in a decrease in electromagnetic wave absorption performance. However, in the present disclosure, since the laminate has the above-mentioned configuration, even if "PEDOT / PSS" is used as the conductive polymer, as shown in FIG. 4, in a scanning electron microscope (SEM)-energy dispersive X-ray analyzer (EDX) image of a cross section cut in the thickness direction of the electromagnetic wave absorbing nonwoven fabric of the embodiment, the conductive polymer is continuously attached to the fiber surface of each layer from the surface to the inside of the laminate. As a result, it is presumed that the electromagnetic wave absorbing nonwoven fabric of the present disclosure has excellent electromagnetic wave absorbing properties. Furthermore, in the present disclosure, the laminate has an SB layer (A) and an MB layer (B). The material of each of the SB layer (A) and the MB layer (B) is a nonwoven fabric. The MB layer (B), which is prone to fluffing, is protected by the SB layer (A) which has a relatively large fiber diameter. When the average fiber diameter of the SB layer (A) is equal to or greater than the lower limit, the mechanical properties of the laminate are improved and a decrease in thickness of the laminate during compression processing is suppressed. As a result, it is presumed that the electromagnetic wave-absorbing nonwoven fabric of the present disclosure has superior bending durability to conventional configurations including a noise suppression sheet. From the above, it is presumed that the electromagnetic wave-absorbing nonwoven fabric of the present disclosure has excellent electromagnetic wave absorption properties and bending durability for electromagnetic waves in the high frequency band (for example, 5 GHz).

[0016] Because the electromagnetic wave-absorbing nonwoven fabric of the present disclosure has the above-mentioned configuration, it can maintain good electromagnetic wave absorbing performance and sound absorbing function even in environments where bending may occur. This effect is presumably due to the above-mentioned and the following reasons, but is not limited to these. The air permeability of the laminate is 5.0 to 48.0 [cc / cm 2·sec]. In this range of air permeability, the sound incidence surface resistance can be reduced. In addition, the average fiber diameter of the first spunbond layer (A) of 20 μm to 50 μm is relatively large among general spunbond nonwoven fabrics. It is presumed that this configuration is also effective in reducing the sound incidence surface resistance. Furthermore, since the average fiber diameter of the second meltblown layer (B) is smaller than the average fiber diameter of the first spunbond layer (A), it is presumed to contribute to improving the sound absorption over a wide frequency range and reducing the variation in the sound absorption rate in the frequency range. Furthermore, when a laminate coated with a conductive polymer paint has all of these configuration combinations, clogging of the conductive polymer on the surface or inside of the laminate can be suppressed, and the adhesion state to the fiber surface is not uneven, and as a result, it is presumed that excellent electromagnetic wave absorption performance and sound absorption performance can be achieved. From the above, it is presumed that the electromagnetic wave-absorbing nonwoven fabric disclosed herein can maintain good electromagnetic wave absorbing performance and sound absorbing function even in environments where bending may occur.

[0017] The air permeability of the laminate, which is an electromagnetic wave absorbing nonwoven fabric, is 5.0 [cc / cm 2 sec]~48.0[cc / cm 2 ·sec. When the laminate to which the conductive polymer is attached has an air permeability in the above range, the electromagnetic wave absorbing nonwoven fabric has excellent electromagnetic wave absorbing properties. Furthermore, the electromagnetic wave absorbing nonwoven fabric further has a sound absorbing function and a filtering function. The air permeability of the electromagnetic wave-absorbing nonwoven fabric is appropriately selected depending on the application of the electromagnetic wave-absorbing nonwoven fabric, so long as it is within the above range. From the viewpoint of suppressing clogging of the conductive polymer and obtaining a better sound absorbing function, the air permeability of the electromagnetic wave-absorbing nonwoven fabric is preferably 6.0 [cc / cm 2 sec]~28.0[cc / cm 2 ·sec], and more preferably 8.0 [cc / cm 2 sec]~23.0[cc / cm 2 ·sec]. The air permeability of the electromagnetic wave absorbing nonwoven fabric is 6.0 [cc / cm 2 sec]~28.0[cc / cm 2 ·sec], it can exhibit sufficient performance as a sound absorbing material. The air permeability of the electromagnetic wave absorbing nonwoven fabric is 5.0 [cc / cm 2 sec]~48.0[cc / cm 2 ·sec] can be adjusted by selecting the average fiber diameter, thickness, basis weight, and average pore diameter of each layer of the nonwoven fabric and / or the laminate, the amount of conductive polymer applied, and a combination thereof. In particular, by providing an SB layer (A) with a relatively large fiber diameter in the outermost layer of the laminate, with an average fiber diameter of 20 μm to 50 μm, and providing an MB layer (B) with a smaller average fiber diameter in the inner layer, even a conductive polymer with a relatively high viscosity can easily permeate the nonwoven fabric. This makes it possible to suppress clogging of the conductive polymer and obtain excellent electromagnetic wave absorption performance. In addition, sound absorption performance can also be achieved. The method for measuring the air permeability of the electromagnetic wave-absorbing nonwoven fabric is the same as that described in the Examples.

[0018] The electromagnetic wave absorbing nonwoven fabric is a sheet-like material. The thickness of the electromagnetic wave absorbing nonwoven fabric is not particularly limited and is appropriately selected depending on the application of the electromagnetic wave absorbing nonwoven fabric. The thickness of the electromagnetic wave absorbing nonwoven fabric may be 0.1 mm to 1.5 mm, or 0.2 mm to 1.0 mm, from the viewpoints of flexibility and suppression of the conductive polymer from striking through to the back. When within the above range, a more flexible sheet is obtained, enabling a use mode that follows a curved shape. In addition, it is possible to prevent the conductive polymer from seeping out to the back surface of the sheet.

[0019] The average pore size of the laminate, which is the electromagnetic wave-absorbing nonwoven fabric, is not particularly limited, and is preferably 5.0 μm to 50.0 μm, more preferably 8.0 μm to 30.0 μm, and even more preferably 10.0 μm to 22.0 μm. If the average pore size of the electromagnetic wave-absorbing nonwoven fabric is 8.0 μm to 30.0 μm, clogging of the conductive polymer can be suppressed, and the air permeability of the electromagnetic wave-absorbing nonwoven fabric can be designed within a predetermined range. As a result, the conductive polymer can be continuously distributed on the fiber surface as shown in FIG. 4, and the electromagnetic wave absorption performance can be improved. The method for measuring the average pore size of the electromagnetic wave-absorbing nonwoven fabric is the same as that described in the examples.

[0020] The electromagnetic wave absorbing nonwoven fabric may be the laminate itself, or may further comprise an optional layer in addition to the laminate.

[0021] (1.1) Laminate The electromagnetic wave absorbing nonwoven fabric comprises a laminate having a conductive polymer attached thereto.

[0022] (1.1.1) Conductive polymers The conductive polymer is not particularly limited as long as it has the above-mentioned conductivity, and is appropriately selected according to the application of the electromagnetic wave absorbing nonwoven fabric and the material of the laminate. The conductive polymer is not particularly limited, but examples thereof include polypyrrole, polythiophene, polyacetylene, polyaniline, etc. Among them, the conductive polymer preferably contains PEDOT / PSS, and more preferably is PEDOT / PSS. PEDOT / PSS is hydrophilic. As the PEDOT-PSS, for example, the PEDOT-PSS described in International Publication No. 2013 / 073673 can be used. The PEDOT / PSS may be a commercially available product.

[0023] The weight of the conductive polymer in the laminate is not particularly limited and is appropriately selected depending on the application of the electromagnetic wave absorbing nonwoven fabric. From the viewpoint of electromagnetic wave absorbing performance and air permeability, the weight of the conductive polymer in the laminate is preferably 0.001 g / m 2 ~5.0g / m 2 , more preferably 0.01 g / m 2 In the electromagnetic wave-absorbing nonwoven fabric of the present invention, even if the weight of the conductive polymer attached is relatively high, the conductive polymer can be continuously dispersed and applied to the fibers of the nonwoven fabric laminate as shown in FIG.

[0024] The degree of adhesion of the conductive polymer is appropriately selected depending on the application of the electromagnetic wave absorbing nonwoven fabric. When the electromagnetic wave absorbing nonwoven fabric is required to have superior electromagnetic wave absorbing properties, the conductive polymer may cover the entire surface of each of the multiple fibers, or may fill multiple gaps between the fibers.

[0025] The conductive polymer is attached to the laminate, for example, by applying a conductive polymer paint to the surface of the SB layer (A) of the laminate and drying it. The degree of adhesion of the conductive polymer can be adjusted by the concentration of the conductive polymer paint, the amount of the conductive polymer paint applied, the number of applications, etc.

[0026] "The amount of conductive polymer attached per unit area" refers to the value obtained by subtracting the amount of conductive polymer attached per unit area of ​​sample (b) obtained by removing the conductive polymer from sample (a) from the amount of conductive polymer attached per unit area of ​​sample (a). For example, the amount of conductive polymer attached per unit area of ​​an electromagnetic wave-absorbing nonwoven fabric refers to the value obtained by subtracting the amount of conductive polymer attached per unit area of ​​a laminate obtained by removing the conductive polymer from the electromagnetic wave-absorbing nonwoven fabric from the amount of conductive polymer attached per unit area of ​​the electromagnetic wave-absorbing nonwoven fabric.

[0027] The method of applying and drying the conductive polymer coating material is not particularly limited and may be any known method. The application method is not particularly limited and may include immersion application (e.g., dip coating), spray application (e.g., spray coating), rotation application (e.g., spin coating), slit coating, curtain coating, gravure coating, flexo coating, etc.

[0028] The conductive polymer coating material may contain a solvent. The solvent is appropriately selected depending on the type of conductive polymer, and examples of the solvent include water, ethanol, and propyl alcohol. The solvent may be used alone or in combination of two or more kinds.

[0029] The conductive polymer coating material may contain a known binder resin in order to improve the fixation and stability of the conductive polymer to the fibers.

[0030] The following describes the case where the conductive polymer is PEDOT / PSS.

[0031] The concentration of the conductive polymer is preferably 0.001% by mass to 1.5% by mass, more preferably 0.1% by mass to 1.2% by mass, and even more preferably 0.5% by mass to 1.0% by mass, based on the total amount of the conductive polymer coating material. If the concentration of the conductive polymer coating material is 0.001% by mass to 1.5%, it is possible to ensure coatability and to exhibit electromagnetic wave absorbing performance. The coating amount of the conductive polymer paint is preferably 0.5 g / m 2 ~2.0g / m 2 , more preferably 1.0 g / m 2 ~1.5g / m 2 The coating weight of the conductive polymer paint is 0.5 g / m 2 ~2.0g / m 2 If so, better electromagnetic wave absorbing performance can be exhibited. The viscosity of the conductive polymer paint is preferably 30 mp / s to 140 mp / s. If the viscosity of the conductive polymer paint is 30 mp / s to 140 mp / s, it can be applied uniformly and breathability can be ensured.

[0032] (1.1.2) Laminate The laminate is a sheet-like object. The laminate has at least an SB layer (A) and an MB layer (B). The laminate may have a layer structure of three or more layers. The layer constituting the laminate may be a layer made of a nonwoven fabric. Details of the layer structure of the laminate will be described later.

[0033] The thickness of the laminate is not particularly limited and is appropriately selected depending on the application of the laminate. The thickness of the laminate may be 0.1 mm to 2.0 mm, or 0.3 mm to 1.0 mm.

[0034] The laminate has a plurality of embossed portions, and the embossed area ratio of the laminate is preferably 5% to 35%. By appropriately disposing the embossed portions on the surface of the outermost layer of the laminate, the coating liquid can be retained during the coating of the conductive polymer, and the coating liquid can be uniformly permeated into the laminate. The embossed area ratio of the laminate is preferably 10% to 28%, more preferably 15% to 25%. The embossed portion is recessed relative to the non-embossed portion of the surface of the laminate. When the embossed area ratio is 10% to 28%, the conductive polymer coating material can accumulate on the embossed portion at one time and continuously impregnate the fibers of the non-embossed portion around the embossed portion due to interfacial tension. As a result, the conductive polymer attached to the fibers is likely to form a network. This improves the electromagnetic wave absorption performance and surface resistance of the conductive polymer attached to the fibers.

[0035] The "embossed portion" refers to a portion where a part of a plurality of fibers is thermally bonded to form a film. The shape of the embossed portion may be a circle, an ellipse, an oval, a square, a diamond, a rectangle, a rectangle, or a continuous shape based on these shapes. The embossed portion is formed by subjecting the laminate to an embossing process (thermocompression processing process). The embossing process is a known method. The "embossed area ratio" refers to the ratio of the total area of ​​multiple embossed parts to the area of ​​the nonwoven fabric observed by taking a test piece measuring 10 mm x 10 mm from the nonwoven fabric and observing the contact surface of the test piece with the embossing roll under an electron microscope (magnification: 100x).

[0036] When the laminate has a plurality of embossed portions and the embossed area ratio of the laminate is 5% to 35%, the area (hereinafter also referred to as "size") of each of the plurality of embossed portions is 0.1 mm 2 ~1.5mm 2 This makes it possible to hold the coating liquid during coating of the conductive polymer, and allows the coating liquid to permeate uniformly into the laminate. From the viewpoint of coating liquid retention and uniform permeation, the area of ​​each of the plurality of embossed portions is preferably 0.1 mm 2 ~1.5mm 2 , more preferably 0.3 mm 2 ~1.0mm 2 It is.

[0037] The resin constituting the fibers of the laminate is not particularly limited as long as it is a thermoplastic resin, and examples thereof include polyolefin resins, polyalkylene terephthalate resins (e.g., polyethylene terephthalate, polybutylene terephthalate, polytrimethylene terephthalate, etc.), polyamide resins (e.g., nylon 6, nylon 66, etc.), polyoxymethylene ether resins (e.g., polyoxymethylene, etc.), polyketone resins (e.g., polyether ketone, etc.), thermoplastic polyimide resins, etc. These resins can be used alone or in combination of two or more.

[0038] Among them, the resin constituting the fibers of the laminate is preferably a polyolefin-based thermoplastic resin from the viewpoints of high strength, easy adjustment to a moderate melt viscosity, and easy molding of the nonwoven fabric and its laminate, and more preferably contains a polypropylene-based resin from the viewpoint of reducing the resistance of the conductive nonwoven fabric, and is even more preferably a polypropylene-based resin. In addition, when a hydrophilic conductive polymer such as PEDOT / PSS (hereinafter, a hydrophilic conductive polymer paint is also referred to as a "hydrophilic conductive polymer paint") is applied to a laminate using a hydrophobic polypropylene-based resin, the breathability of the laminate can be secured more than when the fibers of the laminate are hydrophilic (for example, when the fibers of the laminate are polyethylene terephthalate), and as a result, a laminate coated with a conductive polymer having good electromagnetic wave absorption performance and sound absorption function can be obtained.

[0039] The polyolefin resin may be a homopolymer of an α-olefin, a copolymer of two or more kinds of α-olefins, or a mixture of two or more kinds selected from these. Examples of the α-olefin include ethylene, propylene, 1-butene, 1-pentene, 1-hexene, isopentene, 4-methyl-1-pentene, 3-methyl-1-pentene, 1-octene, 1-decene, 1-hexadecene, 1-octadecene, and 1-eicosene. The polypropylene-based resin may be a homopolymer of propylene, or a copolymer of propylene and other α-olefins copolymerizable therewith. Examples of the α-olefin include ethylene, 1-butene, 1-pentene, 1-hexene, 1-octene, and 4-methyl-1-pentene. The carbon number of the α-olefin is preferably 2 to 8. When the polypropylene-based resin is a copolymer of propylene and an α-olefin, the α-olefin of the copolymer may be one or more selected from the above-mentioned α-olefins.

[0040] The thermoplastic resin (e.g., propylene-based polymer, etc.) used in the present disclosure may be a raw material derived from biomass. Since the raw material derived from biomass is a carbon-neutral material, the environmental load in the production of the spunbond nonwoven fabric can be reduced. Monomers that are raw materials for biomass-derived thermoplastic resins can be obtained by cracking biomass naphtha or synthesizing them from biomass-derived ethylene. The biomass-derived thermoplastic resins can be obtained by polymerizing the biomass-derived monomers synthesized in this manner in the same manner as in the case of using conventionally known petroleum-derived thermoplastic resins. A thermoplastic resin polymer synthesized using a bio-derived monomer as a raw material is a biomass-derived thermoplastic polymer. The content of the bio-derived thermoplastic polymer in the raw material monomer is more than 0 mass% relative to the total amount of the raw material monomer, and may be 100 mass% or less. The "biomass degree" indicates the content of carbon derived from biomass, and is calculated by measuring radioactive carbon (C14). Carbon dioxide in the atmosphere contains a certain percentage of C14 (approximately 105.5 pMC). Therefore, it is known that the C14 content in plants that grow by absorbing carbon dioxide from the atmosphere (such as corn) is also about 105.5 pMC. It is also known that fossil fuels contain very little C14. Therefore, the content of carbon derived from biomass in the raw material can be calculated by measuring the proportion of C14 in the total carbon atoms in the polymer. The thermoplastic polymer used as the raw material in the present disclosure may include a thermoplastic polymer obtained by recycling, that is, a so-called recycled polymer. The term "recycled polymer" includes polymers obtained by recycling waste polymer products, and can be produced, for example, by the method described in DE 102019127827 (A1). The recycled polymer may contain a marker that identifies it as having been obtained by recycling.

[0041] (1.1.2.1) First Spunbond Layer (A) The laminate has an SB layer (A) composed of continuous fibers or long fibers. The SB layer (A) is one of the outermost layers of the laminate.

[0042] The average fiber diameter of the SB layer (A) is 20 μm to 50 μm. If the average fiber diameter of the SB layer (A) is less than 20 μm, the amount of penetration of the conductive polymer coating material tends to be small, and the conductive polymer may adhere to the laminate surface in a mottled pattern. If the average fiber diameter of the SB layer (A) is more than 50 μm, the conductive polymer coating material easily penetrates the SB layer (A), but the amount of penetration of the conductive polymer coating material tends to be small in the MB layer (B), and the conductive polymer may not penetrate sufficiently into the laminate. The average fiber diameter of the SB layer (A) is preferably 20 μm to 50 μm, more preferably 25 μm to 45 μm, from the viewpoint of more effectively suppressing excessive penetration of the hydrophilic conductive polymer into the inside of the laminate and from the viewpoint of further improving the breathability of the laminate. The method for measuring the average fiber diameter of the SB layer (A) is the same as that described in the Examples.

[0043] The SB layer (A) may be a breathable material. The term "breathable material" means a material having breathability, and is a material having a value measured in accordance with JIS L 1096:2010. 2 sec~250cc / cm 2 Indicates sec.

[0044] The thickness of the SB layer (A) is not particularly limited and is appropriately selected depending on the application of the electromagnetic wave absorbing nonwoven fabric. The thickness of the SB layer (A) is preferably 0.1 mm to 1.0 mm, more preferably 0.2 mm to 0.8 mm, from the viewpoints of coating liquid permeability and bending durability (mechanical strength).

[0045] The basis weight of the SB layer (A) is not particularly limited and is appropriately selected depending on the application of the electromagnetic wave absorbing nonwoven fabric. From the viewpoints of coating liquid permeability and bending durability (mechanical strength), the basis weight of the SB layer (A) is preferably 40 g / cm 2 ~200g / cm 2 , more preferably 60 g / cm 2 ~160g / cm 2 The method for measuring the basis weight of the SB layer (A) is the same as that described in the Examples.

[0046] The basis weight ratio (A) is preferably 40% to 96%. The basis weight ratio (A) indicates the ratio of the basis weight of the first spunbond layer (A) to the basis weight of the laminate. When the basis weight ratio (A) is 40% to 96%, the mechanical properties of the laminate are improved, a decrease in thickness of the laminate during compression processing is suppressed, and sufficient bending durability can be achieved. From the viewpoints of coating liquid permeability and bending durability, the basis weight ratio (A) is more preferably 50% to 90%, and from the viewpoint of improving bending durability, it is further preferably 60% to 85%. Furthermore, the SB layer (A) exerts a better effect by combining a fiber diameter of 20 μm to 50 μm of the SB layer (A) with a basis weight ratio (A) of 40% to 96%, 50% to 90%, or 60% to 85%.

[0047] The average pore size of the SB layer (A) is preferably 11.0 μm or more, which allows the conductive polymer coating material to uniformly permeate the laminate. From the viewpoint of uniform penetration of the conductive polymer coating material, the average pore diameter of the SB layer (A) is more preferably 12 μm to 40 μm, and further preferably 14 μm to 30 μm. The method for measuring the average pore diameter of the SB layer (A) is the same as that described in the Examples.

[0048] The average fiber diameter, thickness, basis weight, and average pore diameter of the SB layer (A) described above indicate the average fiber diameter, thickness, basis weight, and average pore diameter, respectively, of the SB layer (A) in a state in which the conductive polymer is attached.

[0049] The resin constituting the fibers of the SB layer (A) may be the same as those exemplified as the resin constituting the fibers of the laminate. From the viewpoints of high strength, ease of adjustment to an appropriate melt viscosity, and ease of molding of the nonwoven fabric and its laminate, it is more preferable to include a polyolefin-based resin, and from the viewpoints of reducing the resistance of the conductive nonwoven fabric and controlling the penetration of the hydrophilic conductive polymer coating material, it is even more preferable to use a polypropylene-based resin. The propylene-based polymer may have a melt flow rate (MFR: ASTM D-1238, 230°C, load 2160g) in the range of, for example, 1g / 10min to 500g / 10min.

[0050] The form of the fiber of the SB layer (A) may be a composite fiber, a hollow fiber, a modified fiber, a crimped fiber, a split fiber, or the like, as long as the effect of the present disclosure is not impaired. The fiber of the SB layer (A) may contain an additive. Examples of the additive include a heat stabilizer, an ultraviolet absorber, a weather stabilizer, a flame retardant, a water repellent, an oil agent, an antistatic agent, a colorant, and an inorganic substance.

[0051] (1.1.2.2) Second Meltblown Layer (B) The laminate has an MB layer (B) which is a continuous fiber or a long fiber. When the laminate has a two-layer structure, the MB layer (B) is the other outermost layer of the laminate. When the laminate has a three-layer or more layer structure, the MB layer (B) does not have to be the other outermost layer of the laminate.

[0052] The average fiber diameter of the MB layer (B) is smaller than the average fiber diameter of the SB layer (A). The average fiber diameter of a meltblown nonwoven fabric is usually less than 10 μm. The average fiber diameter of a spunbond nonwoven fabric is usually 10 μm or more.

[0053] The MB layer (B) is a nonwoven fabric composed of continuous fibers or long fibers, and tends to have a higher BET specific surface area than other nonwoven fabrics. In addition, the fibers are self-fused uniformly throughout the thickness and surface directions. For these reasons, when the nonwoven fabric is a meltblown nonwoven fabric, the resistance of the conductive nonwoven fabric is further reduced. Furthermore, since the fibers of the MB layer (B) tend to be oriented in approximately one direction, the resistance in the direction of fiber orientation is particularly low. From the viewpoint of obtaining a predetermined air permeability, it is preferable to use the MB layer (B) in the laminate.

[0054] The inventors have found that when the resin constituting the fibers of the MB layer (B) contains a polypropylene-based resin and the conductive polymer coating is hydrophilic, the smaller (thinner) the average fiber diameter of the fibers of the MB layer (B) is, the denser and more water-repellent the layer is, but that from the standpoint of breathability, it is desirable for the average fiber diameter of the fibers to be larger (thicker).

[0055] The average fiber diameter of the MB layer (B) is not particularly limited, and is preferably 0.5 μm to 5.0 μm, more preferably 1.0 μm to 4.0 μm. When the average fiber diameter of the MB layer (B) is 0.5 μm to 5.0 μm and the fiber constituting the MB layer (B) is a polypropylene-based resin described later, the fiber of the MB layer (B) is hydrophobic. When the conductive polymer is PEDOT / PSS, the conductive polymer coating material is hydrophilic. Therefore, excessive penetration of the conductive polymer coating material is suppressed compared to when the fiber of the MB layer (B) is hydrophilic (for example, when the fiber of the MB layer (B) is polyethylene terephthalate). This allows the conductive polymer coating material to adhere more uniformly to the inside of the laminate while ensuring the breathability of the laminate. As a result, the electromagnetic wave absorbing nonwoven fabric has better electromagnetic wave absorbing properties. The method for measuring the average fiber diameter of the MB layer (B) is the same as the method described in the Examples.

[0056] The MB layer (B) may be a breathable material.

[0057] The thickness of the MB layer (B) is not particularly limited and is appropriately selected depending on the application of the electromagnetic wave absorbing nonwoven fabric. The thickness of the MB layer (B) is preferably 0.02 mm to 0.40 mm, more preferably 0.05 mm to 0.30 mm, from the viewpoints of suppressing strike-through of the conductive polymer and ensuring the breathability of the sheet.

[0058] The basis weight of the MB layer (B) is not particularly limited and is appropriately selected depending on the application of the electromagnetic wave absorbing nonwoven fabric. The basis weight of the MB layer (B) is preferably 2 g / cm from the viewpoints of suppressing the strike-through of the conductive polymer and ensuring the breathability of the sheet. 2 ~30g / cm 2 , more preferably 5 g / cm 2 ~25g / cm 2 The method for measuring the basis weight of the MB layer (B) is the same as that described in the Examples.

[0059] The basis weight ratio (B) is preferably 1% to 35%. The basis weight ratio (B) indicates the ratio of the basis weight of the MB layer (B) to the basis weight of the laminate. By setting the basis weight ratio (B) to 1% to 35%, it is possible to suppress strike-through of the conductive polymer and ensure necessary breathability. The basis weight ratio (B) is preferably 2% to 25%, more preferably 3% to 15%, from the viewpoint of achieving both coatability and breathability.

[0060] The average pore diameter of the MB layer (B) is not particularly limited and is appropriately selected depending on the application of the electromagnetic wave absorbing nonwoven fabric. From the viewpoint of compatibility between coatability and breathability, the average pore diameter of the MB layer (B) is preferably 5 μm to 50 μm, more preferably 10 μm to 40 μm. The method for measuring the average pore diameter of the MB layer (B) is the same as that described in the Examples.

[0061] The average fiber diameter, thickness, basis weight, and average pore diameter of the MB layer (B) described above each indicate the average fiber diameter, thickness, basis weight, and average pore diameter, respectively, of the MB layer (B) in a state in which the conductive polymer is attached.

[0062] Examples of the resin constituting the fibers of the MB layer (B) include the same resins as those exemplified as the resin constituting the fibers of the SB layer (A).

[0063] Among them, the resin constituting the fiber of the MB layer (B) is more preferably a polyolefin-based resin from the viewpoints of high strength, ease of adjustment to an appropriate melt viscosity, and ease of molding of the nonwoven fabric and its laminate, and is even more preferably a polypropylene-based resin from the viewpoints of reducing the resistance of the conductive nonwoven fabric and controlling the penetration of the hydrophilic conductive polymer coating material. The propylene-based resin constituting the fiber of the MB layer (B) preferably has a melt flow rate (MFR: ASTM D-1238, 230°C, load 2160g) of, for example, 10g / 10min to 4000g / 10min, more preferably 15g / 10min to 2000g / 10min.

[0064] The fiber form of the MB layer (B) may be the same as the fiber form of the SB layer (A) as exemplified within the scope of the present disclosure. The fiber of the MB layer (B) may contain an additive. Examples of the additive include the same as the additives of the SB layer (A).

[0065] (1.1.2.3) Third Spunbond Layer (C) The laminate preferably further comprises a third spunbond layer (C) (hereinafter, "SB layer (C)") laminated on the side opposite to the first spunbond layer (A) of the second meltblown layer (B). The average fiber diameter of the third spunbond layer (C) is smaller than the average fiber diameter of the first spunbond layer (A). When the laminate further comprises the SB layer (C), the MB layer (B) is protected, and the degree to which the MB layer fibers break and fall off in a bending durability test is improved. Therefore, the SB layer (C) can improve the bending durability of the electromagnetic wave absorbing nonwoven fabric. When the average fiber diameter of the third spunbond layer (C) is smaller than the average fiber diameter of the first spunbond layer (A), the strike-through of the conductive polymer can be suppressed.

[0066] The average fiber diameter of the SB layer (C) is appropriately selected according to the average fiber diameter of the SB layer (A). The subtraction value (hereinafter also referred to as the "first subtraction value") obtained by subtracting the average fiber diameter of the SB layer (C) from the average fiber diameter of the SB layer (A) may be 5 μm to 10 μm, or 7 μm to 15 μm. The average fiber diameter of the SB layer (C) is the same as that described in the Examples.

[0067] The average fiber diameter of the SB layer (C) is preferably 10 μm to 25 μm, more preferably 12 μm to 22 μm. If the average fiber diameter of the SB layer (C) is 12 μm to 22 μm, the bending durability and coatability of the laminate are more excellent.

[0068] The SB layer (C) may be a breathable material.

[0069] The thickness of the SB layer (C) is not particularly limited and is appropriately selected depending on the application of the electromagnetic wave absorbing nonwoven fabric. From the viewpoints of bending durability and productivity, the thickness of the SB layer (C) is preferably 0.10 mm to 0.45 mm, more preferably 0.15 mm to 0.35 mm.

[0070] The basis weight of the SB layer (C) is not particularly limited and is appropriately selected depending on the application of the electromagnetic wave absorbing nonwoven fabric. From the viewpoints of bending durability and productivity, the basis weight of the SB layer (C) is preferably 5 g / cm 2 ~50g / cm 2 , more preferably 10 g / cm 2 ~30g / cm 2 The method for measuring the basis weight of the SB layer (C) is the same as that described in the Examples.

[0071] The basis weight ratio (C) is not particularly limited and is appropriately selected depending on the application of the electromagnetic wave absorbing nonwoven fabric. The basis weight ratio (C) indicates the ratio of the basis weight of the SB layer (C) to the basis weight of the laminate. From the viewpoints of bending durability and productivity, the basis weight ratio (C) is preferably 5% to 30%, more preferably 8% to 25%.

[0072] The average fiber diameter, thickness, and basis weight of the SB layer (C) described above respectively indicate the average fiber diameter, thickness, and basis weight of the SB layer (C) in a state in which the conductive polymer is adhered.

[0073] The weight of the conductive polymer in the laminate is 0.001 g / m2 relative to the total weight of the laminate, which is an electromagnetic wave absorbing nonwoven fabric. 2 ~5.0g / m 2 and the conductive polymer of the third spunbond layer (C) preferably has a lower weight per unit area than the conductive polymer of the other layers. The other layer refers to a layer other than the third spunbond layer (C) among the multiple layers included in the laminate. Specifically, when the laminate is composed of the SB layer (A), the MB layer (B), and the SB layer (C), the "other layer" refers to each of the SB layer (A) and the MB layer (B). When the laminate is composed of the SB layer (A), the MB layer (B), the SB layer (C), and a fourth spunbond layer (D) (hereinafter also referred to as "SB layer (D)") described later, the "other layer" refers to each of the SB layer (A), the MB layer (B), and the SB layer (D). The conductive polymer coating weight of the laminate is 0.001g / m 2 ~5.0g / m 2 Since the conductivity of the conductive polymer in the SB layer (C) is lower than that of the conductive polymer in the other layers, clogging of the conductive polymer is prevented, and the electromagnetic wave absorbing nonwoven fabric can have a predetermined air permeability.

[0074] Examples of the resin constituting the fibers of the SB layer (C) include the same resins as those exemplified as the resin constituting the fibers of the SB layer (A).

[0075] Among them, the resin constituting the fibers of the SB layer (C) is more preferably a polyolefin resin from the viewpoints of high strength, ease of adjustment to an appropriate melt viscosity, and ease of molding of the nonwoven fabric and its laminate, and is even more preferably a polypropylene resin from the viewpoints of reducing the resistance of the conductive nonwoven fabric and controlling the penetration of the hydrophilic conductive polymer coating material. The propylene polymer may have a melt flow rate (MFR: ASTM D-1238, 230°C, load 2160g) in the range of, for example, 1g / 10min to 500g / 10min.

[0076] The fiber form of the SB layer (C) may be the same as the exemplified fiber form of the SB layer (A) within the scope of the present disclosure. The fiber of the SB layer (C) may contain an additive. Examples of the additive include the same as the exemplified additives of the SB layer (A).

[0077] (1.1.2.4) Fourth Spunbond Layer (D) The laminate preferably further comprises a fourth spunbond layer (D) between the first spunbond layer (A) and the second meltblown layer (B), the fourth spunbond layer (D) having an average fiber diameter smaller than the average fiber diameter of the first spunbond layer (A). By further having the SB layer (D), the conductive polymer can easily penetrate into the laminate, and the conductive polymer can be distributed more uniformly inside the laminate, thereby enabling the laminate to exhibit higher electromagnetic wave absorption performance.

[0078] The average fiber diameter of the SB layer (D) is appropriately selected according to the average fiber diameter of the SB layer (A). The subtraction value (hereinafter also referred to as the "second subtraction value") obtained by subtracting the average fiber diameter of the SB layer (D) from the average fiber diameter of the SB layer (A) may be 5 μm to 10 μm, or 12 μm to 22 μm. The average fiber diameter of the SB layer (D) is the same as that described in the Examples.

[0079] The average fiber diameter of the SB layer (D) is preferably 10 μm to 25 μm, more preferably 12 μm to 22 μm. If the average fiber diameter of the SB layer (D) is 12 μm to 22 μm, the uniformity of penetration of the conductive polymer is more excellent. Furthermore, the bending durability of the electromagnetic wave absorbing nonwoven fabric is further improved.

[0080] The SB layer (D) may be a breathable material.

[0081] The thickness of the SB layer (D) is not particularly limited and is appropriately selected depending on the application of the electromagnetic wave absorbing nonwoven fabric. From the viewpoint of the uniformity of penetration of the conductive polymer, the thickness of the SB layer (D) is preferably 0.10 mm to 0.45 mm, more preferably 0.15 mm to 0.35 mm.

[0082] The basis weight of the SB layer (D) is not particularly limited and is appropriately selected depending on the application of the electromagnetic wave absorbing nonwoven fabric. From the viewpoint of the uniformity of penetration of the conductive polymer, the basis weight of the SB layer (D) is preferably 5 g / cm. 2 ~50g / cm 2 , more preferably 10 g / cm 2 ~30g / cm 2 The method for measuring the basis weight of the SB layer (D) is the same as that described in the Examples.

[0083] The basis weight ratio (D) is not particularly limited and is appropriately selected depending on the application of the electromagnetic wave absorbing nonwoven fabric. The basis weight ratio (D) indicates the ratio of the basis weight of the SB layer (D) to the basis weight of the laminate. From the viewpoint of the uniformity of penetration of the conductive polymer, the basis weight ratio (D) is preferably 5% to 30%, more preferably 8% to 25%.

[0084] The average fiber diameter, thickness, and basis weight of the SB layer (D) described above respectively indicate the average fiber diameter, thickness, and basis weight of the SB layer (D) in a state in which the conductive polymer is attached.

[0085] Examples of the resin constituting the fibers of the SB layer (D) include the same resins as those exemplified as the resin constituting the fibers of the SB layer (A).

[0086] Among them, the resin constituting the fibers of the SB layer (D) is more preferably a polyolefin resin from the viewpoints of high strength, ease of adjustment to an appropriate melt viscosity, and ease of molding of the nonwoven fabric and its laminate, and is even more preferably a polypropylene resin from the viewpoints of reducing the resistance of the conductive nonwoven fabric and controlling the penetration of the hydrophilic conductive polymer coating material. The propylene polymer may have a melt flow rate (MFR: ASTM D-1238, 230°C, load 2160g) in the range of, for example, 1g / 10min to 500g / 10min.

[0087] The fiber form of the SB layer (D) may be the same as the exemplified fiber form of the SB layer (A) within the scope of the present disclosure. The fiber of the SB layer (D) may contain an additive. Examples of the additive include the same as the exemplified additives of the SB layer (A).

[0088] (1.1.2.5) Preferred embodiments The resin used in the laminate is preferably a polyolefin resin. As a result, the multiple fibers contained in the laminate have hydrophobicity. Therefore, when applying a hydrophilic conductive polymer coating to the laminate, excessive penetration of the conductive polymer coating into the laminate is suppressed compared to when the multiple fibers are hydrophilic. Therefore, the conductive polymer is likely to adhere precisely and uniformly to the fibers on the surface and inside of the laminate. As a result, the electromagnetic wave absorbing nonwoven fabric of the present disclosure has better electromagnetic wave absorbing properties.

[0089] In the present disclosure, the term "resin used in the laminate" means that the resin constituting the fibers contained in all layers constituting the laminate is a polyolefin-based resin. When the laminate has an SSMS structure, the resin constituting the fibers contained in each of the SB layer (A), SB layer (D), MB layer (B), and SB layer (C) is a polyolefin-based resin. When the laminate has an SMS structure, the resin constituting the fibers contained in each of the SB layer (A), MB layer (B), and SB layer (C) is a polyolefin-based resin. When the laminate has an SSM structure, the resin constituting the fibers contained in each of the SB layer (A), SB layer (D), and MB layer (B) is a polyolefin-based resin. When the laminate has an SM structure, the resin constituting the fibers contained in each of the SB layer (A) and MB layer (B) is a polyolefin-based resin.

[0090] (1.1.2.6) First embodiment An example of the laminate of the present disclosure will be described with reference to FIG. 1A. The laminate 10A according to the first embodiment of the present disclosure has an SSMS structure. In detail, as shown in FIG. 1A, the laminate 10A is formed by laminating an SB layer (A) 11, an SB layer (D) 12, an MB layer (B) 13, and an SB layer (C) 14 in this order. The SB layer (A) 11 is one of the outermost layers of the laminate 10A. The SB layer (C) 14 is the other outermost layer of the laminate 10A. The laminate 10A has a plurality of embossed portions 15. The laminate 10A is integrated by the plurality of embossed portions 15.

[0091] Examples of the SB layer (A) 11 include the same as those exemplified as the SB layer (A). Examples of the SB layer (D) 12 include the same as those exemplified as the SB layer (D). Examples of the MB layer (C) 13 include the same as those exemplified as the MB layer (B). Examples of the SB layer (D) 14 include the same as those exemplified as the SB layer (C).

[0092] When the laminate 10A has an SSMS structure, the MB layer (B) can be protected when folded by protecting the front and rear of the MB layer (B) with SB layers, improving bending durability. In addition, the hydrophilic conductive polymer paint can easily penetrate into the laminate and can be applied more densely to the surface and inside of the laminate. In other words, the hydrophilic conductive polymer can adhere more uniformly to the inside of the laminate. As a result, the electromagnetic wave absorbing nonwoven fabric has better electromagnetic wave absorbing properties. Furthermore, the size relationship of each layer, such as the average fiber diameter, basis weight, and average pore diameter, and their combinations can improve the electromagnetic wave absorbing performance and sound absorbing performance.

[0093] (1.1.2.7) Second embodiment An example of the laminate of the present disclosure will be described with reference to FIG. 1B. A laminate 10B according to a second embodiment of the present disclosure has an SMS structure. The laminate 10B has the same configuration as the laminate 10A, except that it does not have an SB layer (D) 12. The laminate 10B is formed by laminating an SB layer (A) 11, an MB layer (B) 13, and an SB layer (C) 14 in this order. The laminate 10B has a plurality of embossed portions 15. The plurality of embossed portions 15 form the laminate 10B into an integrated unit.

[0094] When the laminate 10B has an SMS structure, the MB layer (B), which has a smaller average fiber diameter than the other layers, is protected on both sides by the SB layer, thereby improving the mechanical properties of the laminate, suppressing the reduction in thickness of the laminate during compression processing, and improving bending durability.

[0095] (1.1.2.8) Third embodiment An example of the laminate of the present disclosure will be described with reference to FIG. 1C. A laminate 10C according to a third embodiment of the present disclosure has an SSM structure. The laminate 10C has the same configuration as the laminate 10A, except that it does not have an SB layer (C) 14. The laminate 10C is formed by laminating an SB layer (A) 11, an SB layer (D) 13, and an MB layer (B) 13 in this order. The laminate 10C has a plurality of embossed portions 15. The plurality of embossed portions 15 form the laminate 10C into an integrated unit.

[0096] When the laminate 10C has an SSM structure, the average fiber diameter of each layer gradually decreases in the order of the outermost layer SB layer (A) 11, the adjacent SB layer (C) 14, and the adjacent MB layer (B) 13. This allows the conductive polymer to penetrate more easily into the interior of the laminate and adhere more uniformly to the surface of the continuous fibers. As a result, the electromagnetic wave absorbing nonwoven fabric has better electromagnetic wave absorption properties. In addition, the basis weight of the spunbond nonwoven fabric decreases in the order of the outermost layer SB layer (A) 11 and the adjacent SB layer (C) 14. The fiber diameter gradient, basis weight gradient, or a combination of these allows the conductive polymer to form a dense layer and improve the continuity of conductivity.

[0097] (1.1.2.9) Fourth embodiment An example of the laminate of the present disclosure will be described with reference to FIG. 1D. A laminate 10D according to a fourth embodiment of the present disclosure has an SM structure. The laminate 10D has the same configuration as the laminate 10A, except that the laminate 10D does not have the SB layer (D) 12 and the SB layer (C) 14. The laminate 10D is formed by laminating an SB layer (A) 11 and an MB layer (B) 13 in this order. The laminate 10D has a plurality of embossed portions 15. The plurality of embossed portions 15 form the laminate 10D into one body.

[0098] When the laminate 10D has an SM structure, it has excellent electromagnetic wave absorption properties for electromagnetic waves in a high frequency band (for example, 5 GHz) and excellent bending durability.

[0099] (1.2) Arbitrary layer The electromagnetic wave absorbing nonwoven fabric may further include an optional layer or may not include an optional layer depending on the application of the electromagnetic wave absorbing nonwoven fabric.

[0100] When the electromagnetic wave-absorbing nonwoven fabric is used as a sound-absorbing material, the electromagnetic wave-absorbing nonwoven fabric preferably comprises an optional layer, such as a resin molded product having a three-dimensional mesh structure, a porous film, a sheet-like material (e.g., paper, woven fabric, knitted fabric, felt, inorganic fiber, etc.), a foam, etc.

[0101] The term "resin molded article having a three-dimensional network structure" refers to a resin molded article having a three-dimensional network structure.

[0102] (1.2.1) Resin molded body having a three-dimensional network structure The resin molded article having a three-dimensional mesh structure may be a resin molded article obtained by molding a resin composition containing a thermoplastic resin into a three-dimensional mesh structure. The thermoplastic resin preferably contains any one of short fibers of an ethylene-based polymer, a propylene-based polymer, and a polyester-based polymer.

[0103] (1.2.2) Porous film Examples of the porous film include a microporous film and a mesoporous film. Examples of the porous film include a resin porous film (e.g., a film made porous by stretching a resin containing a filler or a phase-separated polymer alloy), an inorganic porous film (e.g., a cement porous film), and a film having holes formed therein by a hole-forming process (e.g., needle punching). The air permeability of the porous film can be controlled by adjusting, for example, the thickness, density, pore size, and the like.

[0104] (1.2.3) Inorganic fibres Examples of inorganic fibers include glass fibers and carbon fibers.

[0105] (1.2.4) Foam Examples of foams include rubber foams, polyolefin foams (such as polyethylene foams and polypropylene foams), polyurethane foams, polystyrene foams, and acrylic copolymer foams.

[0106] The air permeability of the foam can be controlled by adjusting, for example, the thickness, density, closed cell ratio, and the like. The foam preferably has an open-cell structure from the viewpoint of increasing the air permeability of the highly breathable layer and from the viewpoint of increasing the sound absorbing properties of the sound absorbing material.

[0107] (1.3) Purpose Applications of electromagnetic wave-absorbing nonwoven fabrics include, for example, sound-absorbing materials, electric wires, wiring for robots, high-voltage wire harnesses for automobiles, wearable sensors, diaper sensors, medical articles (e.g., syringes, drip containers, pipes, test tubes, petri dishes, etc.), filters, etc.

[0108] (2) Products containing electromagnetic wave absorbing nonwoven fabric The electromagnetic wave absorbing nonwoven fabric-containing article of the present disclosure comprises the electromagnetic wave absorbing nonwoven fabric of the present disclosure.

[0109] In the present disclosure, the term "electromagnetic wave absorbing nonwoven fabric-containing article" refers to an article comprising the electromagnetic wave absorbing nonwoven fabric of the present disclosure.

[0110] The electromagnetic wave-absorbing nonwoven fabric-containing article of the present disclosure has the above-mentioned configuration, and therefore has excellent electromagnetic wave absorption properties and bending durability against electromagnetic waves in the high frequency band (for example, 5 GHz).

[0111] Examples of articles containing electromagnetic wave-absorbing nonwoven fabrics include sound absorbing materials, electric wires, wiring for robots, high voltage wire harnesses for automobiles, wearable sensors, diaper sensors, medical articles, filters, and the like.

[0112] The sound-absorbing material absorbs sound and also absorbs electromagnetic waves in a high frequency band (e.g., 5 GHz). The sound-absorbing material can be applied to various applications, such as automobiles, electronic devices, buildings, and homes. The configuration of the sound-absorbing material may be any configuration of a known sound-absorbing material, except that it includes the electromagnetic wave-absorbing nonwoven fabric of the present disclosure.

[0113] The electromagnetic wave absorbing nonwoven fabric for electric wires absorbs electromagnetic waves in a high frequency band (e.g., 5 GHz) by covering an electric wire with the electromagnetic wave absorbing nonwoven fabric. The configuration of the electric wire may be any known configuration of an electric wire, except that the electric wire is provided with the electromagnetic wave absorbing nonwoven fabric of the present disclosure.

[0114] The electromagnetic wave absorbing nonwoven fabric for robot wiring absorbs electromagnetic waves in a high frequency band (e.g., 5 GHz) by covering the robot wiring with the electromagnetic wave absorbing nonwoven fabric. The configuration of the robot wiring may be any known configuration of robot wiring, except that it is provided with the electromagnetic wave absorbing nonwoven fabric of the present disclosure.

[0115] The electromagnetic wave absorbing nonwoven fabric for automobile high voltage wire harnesses aims to reduce noise by covering the wire harness with the electromagnetic wave absorbing nonwoven fabric and absorbs electromagnetic waves in a high frequency band (e.g., 5 GHz). The configuration of the wire harness may be a known configuration of an electric wire, except that it is provided with the electromagnetic wave absorbing nonwoven fabric of the present disclosure.

[0116] The medical article is intended to reduce noise in surgical equipment and absorb electromagnetic waves in a high frequency band (e.g., 5 GHz). The configuration of the medical article may be any configuration of a known medical article, except that it is provided with the electromagnetic wave-absorbing nonwoven fabric of the present disclosure.

[0117] The filter captures solid foreign matter in gas or liquid and absorbs electromagnetic waves in a high frequency band (e.g., 5 GHz). The filter may have any known filter configuration, except that it includes the electromagnetic wave absorbing nonwoven fabric of the present disclosure.

[0118] (3) Sound-absorbing materials The sound-absorbing material of the present disclosure comprises the electromagnetic wave-absorbing nonwoven fabric of the present disclosure.

[0119] The sound-absorbing material of the present disclosure has the above-mentioned configuration, and therefore not only absorbs sound, but also has excellent electromagnetic wave absorption properties for electromagnetic waves in a high frequency band (for example, 5 GHz) and bending durability.

[0120] The configuration of the sound-absorbing material may be any known sound-absorbing material, except that it includes the electromagnetic wave-absorbing nonwoven fabric of the present disclosure. The sound-absorbing material can be used in a variety of applications, such as automobiles, electronic devices, buildings, and homes. EXAMPLES

[0121] The present disclosure will be described in more detail below with reference to examples, although the present disclosure is not limited to these examples.

[0122] [1] Measurement and evaluation methods for various physical properties The methods for measuring and evaluating various physical properties are as follows.

[0123] [1.1] Average fiber diameter For the SB layer (A), ten test pieces measuring 10 mm × 10 mm were taken, and using a microscope (Nikon Corporation, product name: ECLIPSE E400) at a magnification of 50x, the diameters of 30 arbitrary points for each test piece were read in μm units to the first decimal place, and the arithmetic mean value was regarded as the average fiber diameter of the fibers contained in the SB layer (A). For the MB layer (B), the MB layer (B) was peeled off from the laminate, and the fiber diameters (μm) of 30 constituent fibers of the sampled sample were measured at a magnification of 500x or 1000x using a scanning electron microscope (manufactured by Hitachi, Ltd., model name: SU3500), and the arithmetic mean value was regarded as the average fiber diameter of the fibers contained in the MB layer (B).

[0124] [1.2] Metsuke Ten test pieces measuring 100 mm (fiber flow direction: MD) x 100 mm (direction perpendicular to the fiber flow direction (CD)) were taken from each of the electromagnetic wave absorbing nonwoven fabric, SB layer (A), MB layer (B), SB layer (C) and SB (D). The test pieces were taken from 10 locations in the CD direction. Next, the mass [g] of each test piece was measured using a top-pan electronic balance (manufactured by Kensei Kogyo Co., Ltd.) to determine the arithmetic mean value of the mass of each test piece. The average value determined above was then multiplied by 1 m. 2 Convert it to mass per unit [g] and calculate the basis weight [g / m 2 〕.

[0125] [1.3] Average pore diameter The average pore diameter of the electromagnetic wave absorbing nonwoven fabric, SB layer (A) and MB layer (B) was measured by taking five test pieces of each and using a palm porometer made by PMI Co., Ltd. The immersion liquid was Fluorinert FC-43 made by 3M Co., Ltd., and the measurements were made by the half-dry method in accordance with ASTM E1294-8. The arithmetic mean value was taken as the average pore diameter of the sheet and each layer.

[0126] [1.4] Fusion area ratio and size of embossed part The embossed area ratio was measured at three points according to the following procedure, and the average value was taken as the embossed ratio. (1) Select the part of the electromagnetic wave-absorbing nonwoven fabric with the highest embossing rate, cut the electromagnetic wave-absorbing nonwoven fabric to be measured into a 10 cm x 10 cm piece to prepare a measurement sample. If it is not possible to take out a piece of electromagnetic wave-absorbing nonwoven fabric to be measured that is 10 cm x 10 cm in size, take out the largest possible size. (2) With the measurement sample placed horizontally, an observation image is taken. The area ratio of the filmed portion in a 50 mm x 50 mm square of the observation image is measured as the embossed area ratio. The area ratio of the top faces of the multiple convex portions arranged in a regular pattern on the embossing roll can be substituted for the above-mentioned embossed area ratio.

[0127] [1.5] Viscosity of conductive polymer paint The solution viscosity of the conductive polymer paint was measured using a B-type viscometer (cone-plate type viscometer CPA-52Z, Eiko Seiki Co., Ltd.) at 20°C and a shear rate of 2.0 N / sec. Three points were measured, and the average value was taken as the viscosity of the conductive polymer paint.

[0128] [1.6] Breathability In accordance with the fabric testing method for woven and knitted fabrics (JIS-L1096:2010), the amount of air passing through the electromagnetic wave absorbing nonwoven fabric (cm3) was measured using a Frazier air permeability measuring device by Method A (Fragile method). 3 / cm 2 The air volume (cm s) was measured. 3 / cm 2 The measured value of s) was taken as the air permeability of the electromagnetic wave absorbing nonwoven fabric. The layer to be measured was peeled off from the sound-absorbing material, and 10 test pieces were taken. For each test piece, a load of 7g / cm was applied. 2 The thickness was measured at five points, the center and the four corners, using a thickness gauge. The average value of the 50 measured thicknesses was calculated and used as the thickness (mm) of each layer. The total thickness of the entire sound-absorbing material was calculated as the sum of the thicknesses of each layer.

[0129] [1.7] Transmission attenuation rate (5GHz) The transmission attenuation rate (5GHz) of electromagnetic wave absorbing nonwoven fabric was measured by the microstrip line method in accordance with IEC standard 62333-1, 2. In detail, a 10cm x 5cm sample was prepared, the measurement sample was placed on the microstrip line, a load of 500g was applied from above, a high frequency signal (5GHz) was input from a network analyzer onto the microstrip line, and the extent to which the signal was attenuated by the measurement sample was evaluated. The transmission attenuation rate (Rtp) was calculated by taking the difference between the incidence and reflection (the true input amount of the microstrip line) and the ratio of this value to the transmission amount. The acceptable measurement result for the transmission attenuation rate (5GHz) is 8dB or more.

[0130] [1.8] Bending durability According to the MIT testing machine method (JIS P 8115:2001), the electromagnetic wave absorbing nonwoven fabric was repeatedly folded back and forth. The number of times the electromagnetic wave absorbing nonwoven fabric was folded back and forth until it broke was measured. Based on the measured number of times of folding back and forth, the bending durability of the electromagnetic wave absorbing nonwoven fabric was evaluated according to the following criteria. An acceptable evaluation result for bending durability is "A" or "A-".

[0131] [1.8.1] Evaluation criteria for bending durability "A": The number of reciprocating folds was 100,000 or more. "A-": The number of reciprocating folds was 10,000 or more and less than 100,000. "B": The number of reciprocating folds was less than 10,000.

[0132] [1.9] Judgment The electromagnetic wave absorbing nonwoven fabric was evaluated for breathability, average pore size, transmission attenuation rate (5GHz) and bending durability, and if it received the best evaluation in all four items, it was given an "A+". If it received a good evaluation in all four items, it was given an "A". Of the four items, emphasis was placed on the evaluation of bending durability and breathability, and an "A-" was given. If even one of the four items did not meet the acceptable evaluation, it was given a "B". Acceptable evaluation results are "A+", "A" or "A-".

[0133] [1.9.1] Evaluation criteria "A+": The air permeability, average pore size, transmission attenuation rate (5 GHz) and bending durability evaluation were all the best. "A": The air permeability, average pore size, transmission attenuation rate (5 GHz) and bending durability evaluation were all rated as good. "A-": Bending durability and air permeability were near the upper and lower limits of the standard values. "B": The air permeability, average pore size, transmission attenuation rate (5 GHz) and bending durability evaluation did not meet the acceptable standards.

[0134] [2] Examples and Comparative Examples In this example, an electromagnetic wave absorbing nonwoven fabric was obtained as follows.

[0135] [2.1] Example 1 [2.1.1] SB web (C-1) manufacturing process A propylene homopolymer having a melt flow rate (MFR) of 60 g / 10 min measured under conditions of 230°C and 2.16 kg was used to form an SB web (C-1) on a screen by spinlay lamination using a spunbond nonwoven fabric molding machine having a spinneret. The diameter of the spinneret was 0.6 mm. The nozzle temperature for the spinlay lamination was set to 230°C. The SB web (C-1) was the material of the SB layer (C). The average fiber diameter of the SB web (C-1) was 15 μm. The basis weight of the SB web (C-1) was 10 g / m 2 It was.

[0136] [2.1.2] Manufacturing process of MB web (B-1) Next, a propylene homopolymer having a MFR of 400 g / 10 min measured under conditions of 230° C. and 2.16 kg was melted at 280° C. using an extruder. The resulting melt was melt-blown onto the SB web (C-1) to form an MB web (B-1). The temperature of the heated air in the melt-blown lamination was 280° C. The MB web (B-1) was the material of the MB layer (B). The average fiber diameter of the MB web (B-1) was 3 μm. The basis weight of the MB web (B-1) was 5 g / m 2 It was.

[0137] [2.1.3] SB web (D-1) manufacturing process Next, an SB web (D-1) was formed on the MB web (B-1) in the same manner as in the production process of the SB web (C-1). The SB web (D-1) is the material of the SB layer (D). The average fiber diameter of the SB web (D-1) was 15 μm. The basis weight of the SB web (D-1) was 10 g / m 2 As a result, a three-layer laminate was obtained. The three-layer laminate was formed by laminating the SB web (D-1), the MB web (B-1) and the SB web (C-1) in this order.

[0138] [2.1.4] First embossing process Next, the three-layer laminate was sandwiched between an embossing roll and a mirror roll to be integrated. The imprinting area ratio of the embossing roll was 18%. The set temperature of the embossing roll was 145°C. The set temperature of the mirror roll was 150°C. In this way, a three-layer structure (hereinafter also referred to as "SMS structure") nonwoven fabric was obtained. The SMS structure nonwoven fabric is formed by laminating an SB layer (D), an MB layer (B) and an SB layer (C) in this order. The basis weight of the SMS structure nonwoven fabric was 25 g / m 2 It was.

[0139] In the present disclosure, the "imprinted area ratio of the embossing roll" refers to the area ratio of the convex portions formed on the embossing roll relative to the surface area of ​​the embossing roll. The imprinted area ratio of the embossing roll and the embossed area ratio of the laminate are substantially the same.

[0140] [2.1.5] SB web (A-1) manufacturing process Next, a propylene homopolymer having an MFR of 60 g / 10 min measured under conditions of 230°C and 2.16 kg was used to form an SB web (A-1) on the SB layer (D) of the SMS structure nonwoven fabric by spinlay lamination in a spunbond nonwoven fabric molding machine having a spinneret. The nozzle temperature for spinlay lamination was set to 230°C. The SB web (A-1) was the material for the SB layer (A). The average fiber diameter of the SB web (A-1) was 30 μm. The basis weight of the SB web (A-1) was 100 g / m 2 The average pore size of the SB web (A-1) was 16 μm. This resulted in a four-layer laminate. The four-layer laminate was formed by laminating the SB web (A-1), the SB layer (D), the MB layer (B) and the SB layer (C) in this order.

[0141] [2.1.6] Second embossing process Next, the four-layer laminate was sandwiched between an embossing roll and a mirror roll to be integrated. The imprinting area ratio of the embossing roll was 18%. The embossed pattern of the embossing roll was 0.9 mm square. The set temperature of the embossing roll was 155°C. The set temperature of the mirror roll was 160°C. This resulted in a laminate made of a nonwoven fabric with a four-layer structure (hereinafter also referred to as "SSMS structure"). The laminate with the SSMS structure is formed by laminating an SB layer (A), an SB layer (D), an MB layer (B), and an SB layer (C) in this order.

[0142] [2.1.7] Conductive polymer attachment process As the raw material for the conductive polymer paint, we prepared a product called "CV501-1.0" manufactured by Kleva Co., Ltd. The components of "CV501-1.0" are as follows:

[0143] <Ingredients of "CV501-1.0"> Conductive polymer: PEDOT / PSS (Poly(3,4-EthyleneDiOxyThiophene / Poly(4-StyreneSulfonate) ·Solid content concentration: 1.3% by mass ·Shape: Fine particles Solvent: Water ·Viscosity: 50mPa·s~150mPa·s

[0144] The conductive polymer paint raw material was melted by adding a mixture of water, isopropyl alcohol, and diethylene glycol as a solvent, and a binder resin component was added to obtain a conductive polymer paint. The concentration of the conductive polymer was 1%. The viscosity of the conductive polymer paint was 62.8mp / s.

[0145] A conductive polymer paint was applied to the surface of the SB layer (A) of the SSMS structure laminate using a gravure coater. The amount of the conductive polymer paint applied was 25 g / m 2 The conductive polymer coating was then dried to obtain an electromagnetic wave absorbing nonwoven fabric.

[0146] FIG. 2A shows a front image of the electromagnetic wave absorbing nonwoven fabric immediately after the conductive polymer paint was applied to the surface of the SSMS structure laminate. "Immediately after the conductive polymer paint was applied" refers to 30 seconds before the conductive polymer paint was applied to the surface of the SSMS structure laminate. FIG. 2B shows a front image of the electromagnetic wave absorbing nonwoven fabric in a state where the conductive polymer paint has dried on the surface of the SSMS structure laminate. In FIG. 2A and FIG. 2B, the dark parts including the black parts indicate the conductive polymer paint application, the light parts including the white parts indicate the fibers of the laminate, and the regularly formed dots indicate the embossed parts. From FIG. 2A, it was found that the paint accumulated in the embossed parts, and the paint was uniformly attached to the entire surface of the laminate from there. From FIG. 2B, it was found that the conductive polymer was uniformly attached to the entire surface of the laminate.

[0147] [2.1.8] EPMA surface elemental analysis An EPMA (electron beam microanalysis) image of the surface of the SB layer (A) of the electromagnetic wave absorbing nonwoven fabric of Example 1 is shown in Figure 3. Figure 3 shows the mapping results of the sulfur component of "PEDOT / PSS" contained in the conductive polymer paint. The light colored areas (white areas) indicate the sulfur component. The various rectangular areas in the image indicate the embossed parts. From FIG. 3, it can be seen that the conductive polymer is neatly connected in a lattice pattern on the surface of the laminate.

[0148] [2.1.9] SEM-EDX cross-sectional elemental analysis Figure 4 shows an SEM-EDX image of a cross section cut in the thickness direction of the obtained electromagnetic wave absorbing nonwoven fabric. Figure 4 shows the mapping results of the sulfur components of "PEDOT / PSS" contained in the conductive polymer paint. The bright areas (white areas) indicate the sulfur components. Figure 4 shows that the conductive polymer is neatly connected. Unlike conventional conductive polymers, the conductive polymer is distributed in a mesh pattern.

[0149] [2.2] Examples 2 to 5, Example 8, and Comparative Examples 1 to 4 The electromagnetic wave absorbing nonwoven fabrics of Examples 2 to 5, Example 8, and Comparative Examples 1 to 4 were obtained in the same manner as in Example 1, except that the materials of the SB layer (A), SB layer (D), MB layer (B), SB layer (C), embossed portion, and conductive polymer were changed to the materials shown in Table 1. In Comparative Example 4, no conductive polymer deposition was performed.

[0150] In Comparative Example 2, an image of the surface of the electromagnetic wave-absorbing nonwoven fabric in a state where the conductive polymer paint has dried is shown in FIG. 5. In FIG. 5, the dark colored areas including black areas indicate the conductive polymer paint coating, the light colored areas including white areas indicate the fibers of the laminate, and the regularly formed dots indicate the embossed areas. In comparison with the image of the electromagnetic wave-absorbing nonwoven fabric of Example 1 (see FIG. 2B), it can be seen that there are multiple black islands on the surface of the electromagnetic wave-absorbing nonwoven fabric of Comparative Example 2. These islands are an aggregate of the conductive polymer paint coating that has filled multiple gaps between the fibers of the laminate. As shown in Table 1, the air permeability of Comparative Example 2 is lower than that of Example 1. In comparison with FIG. 2B and FIG. 5, it was found that the main cause of this is that the conductive polymer paint coating is packed into multiple gaps between the fibers of the laminate.

[0151] [2.3] Example 6 [2.3.1] Manufacturing process of MB web (B-1) An MB layer (B) was formed on the screen in the same manner as in the preparation process of the MB web (B-1) in Example 1.

[0152] [2.3.2] SB web (A-1) manufacturing process Next, the SB web (A-1) was formed on the MB layer (B) in the same manner as in the preparation process of the SB web (A-1) in Example 1. This resulted in a two-layer laminate. The two-layer laminate was formed by laminating the SB web (A-1) and the MB web (B-1) in this order.

[0153] [2.3.3] Second embossing process Next, the two-layer laminate was integrated in the same manner as in the second embossing process of Example 1. The imprinting area ratio of the embossing roll was 28%. The embossed pattern of the embossing roll was 0.7 mm square. The set temperature of the embossing roll was 155°C. The set temperature of the mirror roll was 160°C. This resulted in a laminate made of a nonwoven fabric with a two-layer structure (hereinafter also referred to as "SM structure"). The SM structure laminate is formed by laminating an SB layer (A) and an MB layer (B) in this order.

[0154] [2.3.4] Conductive polymer attachment process In the same manner as in the conductive polymer adhesion step of Example 1, a conductive polymer coating material was applied onto the surface of the SB layer (A) of the SM structure laminate, and then dried to obtain an electromagnetic wave absorbing nonwoven fabric.

[0155] [2.4] Example 7 [2.4.1] Manufacturing process of MB web (B-1) An MB layer (B) was formed on the screen in the same manner as in the preparation process of the MB web (B-1) in Example 1.

[0156] [2.4.2] SB web (D-1) manufacturing process Next, in the same manner as in the production process of the SB web (D-1) in Example 1, an SB web (D-1) was formed on the MB web (B-1).

[0157] [2.4.3] SB web (A-1) manufacturing process Next, the SB web (A-1) was formed on the SB web (D-1) in the same manner as in the preparation process of the SB web (A-1) in Example 1. This resulted in a three-layered laminate. The three-layered laminate was formed by laminating the SB web (A-1), the SB web (D-1), and the MB web (B-1) in this order.

[0158] [2.4.4] Second embossing process Next, the three-layer laminate was integrated in the same manner as in the second embossing process of Example 1. The imprinting area ratio of the embossing roll was 28%. The embossed pattern of the embossing roll was 0.7 mm square. The set temperature of the embossing roll was 155°C. The set temperature of the mirror roll was 160°C. This resulted in a laminate made of a three-layer structure (hereinafter also referred to as "SSM structure") nonwoven fabric. The laminate with the SSM structure is formed by laminating the SB layer (A), SB layer (D), and MB layer (B) in this order.

[0159] [2.4.5] Conductive polymer attachment process In the same manner as in the deposition of the conductive polymer in Example 1, a conductive polymer coating material was applied onto the surface of the SB layer (A) of the laminate having the SSM structure, and then dried to obtain an electromagnetic wave absorbing nonwoven fabric.

[0160] [2.5] Comparative Example 5 As the electromagnetic wave absorbing nonwoven fabric, a noise suppression sheet manufactured by Tokin Corporation (product name "Bastaraid FG1", material: metal magnetic powder and resin, thickness: 0.05 mmt) was used.

[0161] [2.6] Example 9 [2.6.1] SB web (C-2) manufacturing process A propylene homopolymer having a melt flow rate (MFR) of 60 g / 10 min measured under conditions of 230°C and 2.16 kg was used to form an SB web (C-2) on a screen by spinlay lamination using a spunbond nonwoven fabric molding machine having a spinneret. The diameter of the spinneret was 0.6 mm. The nozzle temperature for the spinlay lamination was set to 230°C. The SB web (C-2) was the material for the SB layer (C). The average fiber diameter of the SB web (C-2) was 20 μm. The basis weight of the SB web (A-2) was 20 g / m 2 It was.

[0162] [2.6.2] Manufacturing process of MB web (B-2) Next, a propylene homopolymer having a MFR of 400 g / 10 min measured under conditions of 230° C. and 2.16 kg was melted at 280° C. using an extruder. The resulting melt was melt-blown onto the SB web (C-2) to form an MB web (B-2). The temperature of the heated air for melt-blown lamination was 280° C. The MB web (B-2) was the material for the MB layer (B). The average fiber diameter of the MB web (B-1) was 3 μm. The basis weight of the MB web (B-2) was 25 g / m 2 It was.

[0163] [2.6.3] SB web (A-2) manufacturing process Next, the SB web (A-2) was formed on the MB web (B-2) in the same manner as in the preparation of the SB web (C-2). The SB web (A-2) was the material of the SB layer (A). The average fiber diameter of the SB web (A-2) was 20 μm. The basis weight of the SB web (A-2) was 40 g / m 2 As a result, a three-layer laminate was obtained. The three-layer laminate was formed by laminating the SB web (A-2), the MB web (B-2) and the SB web (C-2) in this order.

[0164] [2.6.4] Second embossing process Next, the three-layer laminate was integrated in the same manner as in the second embossing process of Example 1. The imprinting area ratio of the embossing roll was 10%. The embossed pattern of the embossing roll was 0.5 mm square. The set temperature of the embossing roll was 155°C. The set temperature of the mirror roll was 160°C. This resulted in a laminate made of a three-layer structure (hereinafter also referred to as "SMS structure") nonwoven fabric. The SMS structure laminate is formed by laminating an SB layer (A), an MB layer (B), and an SB layer (C) in this order.

[0165] [2.6.5] Conductive polymer attachment process In the same manner as in the deposition of the conductive polymer in Example 1, a conductive polymer coating material was applied onto the surface of the SB layer (A) of the laminate having the SMS structure, and then dried to obtain an electromagnetic wave absorbing nonwoven fabric.

[0166] [2.6.6] Measurement of sound absorption coefficient For this sample, optional layer 1 was laminated to produce a sound absorbing material, and the sound absorbing performance was measured and the results are shown in Figure 6. The sound absorption coefficient at 5000 Hz was 0.92, and the average sound absorption coefficient from 1000 Hz to 6300 Hz was 0.73.

[0167] [2.7] Comparative Example 6 In Comparative Example 6, no conductive polymer deposition was performed.

[0168] [2.7.1] Measurement of sound absorption coefficient For this sample, optional layer 1 was laminated to produce a sound absorbing material, and the sound absorbing performance was measured and the results are shown in Figure 6. The sound absorption coefficient at 5000 Hz was 0.96, and the average sound absorption coefficient from 1000 Hz to 6300 Hz was 0.74.

[0169] <Creation of optional layers> As an optional layer, a short fiber nonwoven fabric, which is a resin molded body having a three-dimensional mesh structure, was prepared. 5 parts by mass of propylene polymer short fibers (manufactured by Ube Exsymo Co., Ltd., product name: UC Fiber, average fiber diameter 21 μm, average fiber length 51 mm), 65 parts by mass of polyethylene terephthalate resin short fibers (average fiber diameter 35 μm, average fiber length 51 mm), and 30 parts by mass of polyethylene terephthalate resin short fibers (manufactured by Unitika Co., Ltd., product name: Melty 4080, average fiber diameter 14 μm, average fiber length 51 mm) as binder fibers were mixed, and a web was formed using a fiber spreader and a carding machine, and then multi-layered using a cross-layer machine and treated with a hot air treatment machine set to a gap distance of about 15 mm to obtain a sheet-like nonwoven fabric molded body (optional layer 1) having a thickness of about 15 mm, which contains propylene polymer short fibers and polyethylene terephthalate resin short fibers.

[0170] <Production of sound-absorbing material> The size of the SMS structure laminate and optional layer 1 was adjusted to 300 mm in the MD direction and 300 mm in the CD direction. The laminate and optional layer 1 were laminated in this order so as not to deviate from the 300 mm square, and the ends of these two layers were fused together using an ultrasonic sealer (Honda Electronics Co., Ltd. ultrasonic welding machine SONAC-37) to obtain a sound absorbing material.

[0171] [Evaluation of sound absorption performance] -Sound absorption coefficient measurement A circular test piece of 29 mmφ was taken from any part of the sound absorbing material produced. Then, using an acoustic tube with an inner diameter of 29 mm, the normal incidence sound absorption coefficient was measured when a plane sound wave with a frequency of 1000 Hz to 6300 Hz was perpendicularly incident on the test piece, in accordance with ASTM E 1050, using a normal incidence sound absorption coefficient measuring device (Bruel & Kjaer, TYPE 4206). From the obtained sound absorption coefficient curve of 1000 Hz to 6300 Hz, the normal incidence sound absorption coefficients (hereinafter also simply referred to as "sound absorption coefficients") of 1000 Hz, 1250 Hz, 1600 Hz, 2000 Hz, 2500 Hz, 3150 Hz, 4000 Hz, 5000 Hz, and 6300 Hz were obtained, and the average sound absorption coefficient was calculated.

[0172] [Formula 1] Average sound absorption coefficient = (sound absorption coefficient at 1000Hz + sound absorption coefficient at 1250Hz + sound absorption coefficient at 1600Hz + sound absorption coefficient at 2000Hz + sound absorption coefficient at 2500Hz + sound absorption coefficient at 3150Hz + sound absorption coefficient at 4000Hz + sound absorption coefficient at 5000Hz + 6300Hz) / 9

[0173] [Table 1]

[0174] In Table 1, "noise suppression sheet" refers to a noise suppression sheet manufactured by Tokin Corporation (product name "Bastaraid FG1").

[0175] In Comparative Example 1, the average fiber diameter of the SB layer (A) was outside the range of 20 μm to 50 μm. In Comparative Example 2, the average fiber diameter of the SB layer (A) was outside the range of 20 μm to 50 μm, and the air permeability of the electromagnetic wave absorbing nonwoven fabric was 5.0 [cc / cm 2 sec]~48.0[cc / cm 2 ·sec]. In Comparative Example 3, the air permeability of the electromagnetic wave-absorbing nonwoven fabric was 5.0 [cc / cm 2 sec]~48.0[cc / cm 2·sec]. In Comparative Example 4 and Comparative Example 6, no conductive polymer was attached to the laminate. Therefore, the transmission attenuation rate (5 GHz) of the electromagnetic wave absorbing nonwoven fabrics of Comparative Examples 1 to 4 and Comparative Example 6 was less than 8 dB. In Comparative Example 5, the electromagnetic wave-absorbing nonwoven fabric did not have a laminate to which a conductive polymer was attached, and therefore the bending durability of the electromagnetic wave-absorbing nonwoven fabric of Comparative Example 5 was evaluated as "B." These results show that the electromagnetic wave absorbing nonwoven fabrics of Comparative Examples 1 to 6 are not electromagnetic wave absorbing nonwoven fabrics excellent in electromagnetic wave absorbency and bending durability for electromagnetic waves in the high frequency band.

[0176] In Examples 1 to 9, the electromagnetic wave absorbing nonwoven fabric had a laminate to which a conductive polymer was attached. The laminate had an SB layer (A) and an MB layer (B). The SB layer (A) was one of the outermost layers of the laminate. The air permeability was 5.0 [cc / cm 2 sec]~48.0[cc / cm 2 ·sec]. Therefore, the transmission attenuation rate (5 GHz) of the electromagnetic wave-absorbing nonwoven fabrics of Examples 1 to 5 was 8 dB or more. The bending durability of the electromagnetic wave-absorbing nonwoven fabrics of Examples 1 to 5 was evaluated as "A". As a result, it was found that the electromagnetic wave absorbing nonwoven fabrics of Examples 1 to 9 were excellent in electromagnetic wave absorbing properties for electromagnetic waves in the high frequency band and in bending durability. [Explanation of symbols]

[0177] 1A, 1B, 1C, 1D laminate 11 First spunbond layer (A) 12 Fourth spunbond layer (D) 13 Second meltblown layer (B) 14 Third spunbond layer (C)

Claims

1. a laminate having a conductive polymer attached thereto; The laminate comprises: A first spunbond layer (A) having an average fiber diameter of 20 μm to 50 μm; A second meltblown layer (B) having an average fiber diameter smaller than that of the first spunbond layer (A); having the first spunbond layer (A) is one outermost layer of the laminate; The air permeability is 5.0 [cc / cm 2 ・sec]~48.0[cc / cm 2 .sec].

2. The basis weight ratio (A) is 40% to 96%, The electromagnetic wave absorbing nonwoven fabric according to claim 1, wherein the basis weight ratio (A) indicates the ratio of the basis weight of the first spunbond layer (A) to the basis weight of the laminate.

3. 2. The electromagnetic wave absorbing nonwoven fabric according to claim 1, wherein the average pore size of the laminate is 5.0 μm or more.

4. The laminate further includes a third spunbond layer (C) laminated on the second meltblown layer (B) on a side opposite to the first spunbond layer (A), 2. The electromagnetic wave absorbing nonwoven fabric according to claim 1, wherein the average fiber diameter of the third spunbond layer (C) is smaller than the average fiber diameter of the first spunbond layer (A).

5. The conductive polymer has a coating weight of 0.001 g / m 2 ~5.0g / m 2 and the weight of the conductive polymer in the third spunbond layer (C) is lower than the weight of the conductive polymer in the other layers; The electromagnetic wave absorbing nonwoven fabric according to claim 4, wherein the other layer is a layer other than the third spunbond layer (C) among the multiple layers included in the laminate.

6. the laminate further comprises a fourth spunbond layer (D) between the first spunbond layer (A) and the second meltblown layer (B); 2. The electromagnetic wave absorbing nonwoven fabric according to claim 1, wherein the average fiber diameter of the fourth spunbond layer (D) is smaller than the average fiber diameter of the first spunbond layer (A).

7. The basis weight ratio (B) is 1% to 35%, The electromagnetic wave absorbing nonwoven fabric according to claim 5, wherein the basis weight ratio (B) indicates the ratio of the basis weight of the second meltblown layer (B) to the basis weight of the laminate.

8. The laminate has a plurality of embossed portions, 2. The electromagnetic wave absorbing nonwoven fabric according to claim 1, wherein the embossed area ratio of the laminate is 5% to 35%.

9. The area of ​​each of the plurality of embossed portions is 0.1 mm 2 ~1.5mm 2 The electromagnetic wave absorbing nonwoven fabric according to claim 8 .

10. 2. The electromagnetic wave absorbing nonwoven fabric according to claim 1, wherein the resin used in the laminate is a polyolefin resin.

11. An electromagnetic wave absorbing nonwoven fabric-containing article comprising the electromagnetic wave absorbing nonwoven fabric according to any one of claims 1 to 10.

12. A sound-absorbing material comprising the electromagnetic wave-absorbing nonwoven fabric according to any one of claims 1 to 10.

Citation Information

Patent Citations

  • Electromagnetic wave absorbing adhesive sheet

    JP2020013848A